Repeated administration of low dose isoprenaline on the rat’s cardiovascular system - Rajasegar Anamalley,; Logeswary Rajassageran,; Yasaaswini Apparoo,; Muhammad Haffiz Jauri,; Kamisah Yusof,; Nurhanan Mohd Yunos,; Satirah Zainalabidin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Isoprenaline (ISO) at high doses can cause severe stress to myocardium resulting in an infarct-like necrosis in rats. However, its effects at repeatedly low dose exposure on heart, kidney and aorta are still unclear. Hence, this study was aimed to investigate the effects of repeated administration of low dose ISO on the organs in rats by using Langendorff-perfused isolated hearts, ELISA kits, qPCR and histopathology techniques. Male Wistar rats (n=24) were randomly divided into three groups which were given 5 or 10 mg/kg/day of ISO (ISO 5 and ISO 10, respectively), or normal saline (control) subcutaneously for 14 days. Blood pressure was recorded at day-0, 7 and 14. Heart, aorta, kidneys, and blood were then collected. ISO at both doses significantly increased the heart weight and blood pressure (p<0.05), while the heart rate was significantly decreased (p<0.05). ISO also increased serum troponin and NT-pro-BNP, and decreased vascular relaxation dose-dependently. Group ISO 10 showed significantly increased cardiomyocyte area and cardiac collagen content, as well as reduced serum nitrite (p<0.05). However, ISO at both doses did not affect the cardiac mechanical function, renal oxidative stress, inflammation, as well as renal gene expressions of angiotensin-converting enzyme and angiotensin II type 1 receptor. In conclusion, repeated low dose of ISO significantly causes myocardial injury and reduces vascular function in rats. The findings imply that this rat model could be a suitable model of heart injury without the complication of renal injury.